First-line single-agent panitumumab in frail elderly patients with wild-type KRAS metastatic colorectal cancer and poor prognostic factors: A phase II study of the Spanish Cooperative Group for the Treatment of Digestive Tumours. Issue 11 (July 2015) - Sastre, J.; Massuti, B.; Pulido, G.; Guillén-Ponce, C.; Benavides, M.; Manzano, J.L.; Reboredo, M.; Rivera, F.; Grávalos, C.; Safont, M.J.; Martínez Villacampa, M.; Llovet, P.; et al.
Abstract Background Frail elderly patients with metastatic colorectal cancer (mCRC) are not candidates for chemotherapy. Monotherapy with anti-epidermal growth factor receptor (EGFR) monoclonal antibodies may be an option for these patients with few systemic toxic effects. Patients and methods Single-arm, multicentre, phase II trial including patients ⩾70 years with wild-type (WT) KRAS (exon 2) mCRC, Eastern Cooperative Oncology Group (ECOG) status ⩽ 3, KPC (Köhne Prognostic Classification) – defined intermediate or high risk status, frailty and/or ineligibility for chemotherapy. Patients received panitumumab until progression or unacceptable toxicity. The primary end-point was progression free survival (PFS) rate at 6 months. Results The study included 33 patients (intention-to-treat (ITT) population). Median age: 81 years; sex: 66.7% male; high-risk KPC status: 45.4%. Median treatment duration was 14 weeks and 6-month PFS rate was 36.4% (95% confidence interval (CI): 20.0–52.8). The objective response rate: 9.1% (95% CI: 0–18.9) (all partial responses), and there were 18 stable diseases (54.5%). Median PFS was 4.3 months (95% CI: 2.8–6.4) and median overall survival (OS) was 7.1 months (95% CI: 5.0–12.3). There were no deaths or grade 4–5 adverse events (AEs) related to panitumumab and the most common grade 3-related AE was rash acneiform (15.2%). A significant association between clinical response and RAS status was observed (P = 0.037). In the WT RAS subgroup (WT exons 2, 3, and 4 of KRAS and NRAS, N = 15), 6-month PFS rate was 53.3% (95% CI: 30.1–75.2) and median PFS and OS were 7.9 and 12.3 months, respectively. Conclusions Single-agent panitumumab is active and well tolerated and may be a therapeutic option for high-risk frail elderly patients with WT RAS tumours considered not candidates for chemotherapy (clinicaltrials.gov identifier NCT01126112).